Influence of method of preparation on the activity of La-Ni-Ce mixed oxide catalysts for dry reforming of methane - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Surendar, M.; Lingaiah, N.; Rao, K. S. Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (RSC Advances, 2014)
La-Ni-x-Ce1-x mixed oxide catalysts were prepared by a sol-gel method varying the Ni composition (0 <= x <= 1). The catalysts were characterized by X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), BET surface area, X-ray photoelectron spectroscopy (XPS), temperature-programmed reduction (TPR), H-2 chemisorption and Fourier transform infrared spectroscopy (FT-IR) techniques. CO2 reforming of methane was carried out at atmospheric pressure and 800 degrees C, maintaining a reactant CO2/CH4/N-2 ratio of 80/80/80 (total flow rate = 240 ml min(-1), GHSV of 28 800 h(-1)). The catalysts offered higher activity even at lower Ni compositions. LaNi0.4Ce0.6O3. showed the highest conversion of CH4 and CO2. The H-2/CO ratio in the syngas was stable at 0.85 +/- 0.02. The performance of the sol-gel catalysts was compared with that of the hydrothermally prepared catalysts, reported earlier. High surface area and better Ni dispersion were found to be the reasons for superior activity of the sol-gel catalysts.

Methane reforming with carbon dioxide over La-Ni-x-Ce1-x mixed oxide catalysts - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Upendar, K.; Lingaiah, N.; Rao, Kamaraju Seetha Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
La-Ni-x-Ce1-x mixed oxide (0 <= x <= 1) catalysts have been hydrothermally prepared, characterized by physico-chemical techniques and evaluated for CO2 reforming of methane. High conversions are achieved for both methane and carbon dioxide over the LaNi0.6Ce0.4O3 catalyst tested under the conditions of CO2/CH4/N-2 ratio of 80/80/80. (total flow rate = 240 mL/min), space velocity of 28,800 h(-1) and at a temperature of 800 degrees C. The H-2/CO ratio in the syngas is stable at 0.93 +/- 0.02. Exchanging Ni with Ce, rather than with La as reported in the literature, appears to be a better option for the improved performance of the catalysts.
Keywords: Carbon dioxide reforming; Catalysts; Cerium; Dry reforming; Hydrothermal synthesis; Lanthanum; Methane reforming; Mixed oxides; Nickel